Effect of SiC particle size on hardness and wear behavior of TIG melted hard surface layer AISI Duplex-2205 steel - Paijan, Lailatul Harina; Maleque, Md Abdul; -, Suryanto (The Mattingley Publishing Co., Inc, 2020)
The formation of hard surface layer on AISI Duplex-2205 steel provides a protective coating against wear application. In the present work, SiC particle size with average sizes of 20 µm, 60 µm and 100 µm were used as surface preplacement to AISI Duplex-2205 surface. The purpose of the study is to evaluate the influence of different SiC particle size melted at heat input of 768 J/mm on hardness and wear behavior. The surface characterization, hardness and wear behavior were conducted using scanning electron microscopy, Vickers micro-hardness and reciprocating wear tester, respectively. Characterization of the TIG melted layer reveals the existence of new phases containing a dendritic structure. The surface hardness developed 4 to 6 times higher than substrate hardness (250 Hv) depending on the dendrite population. The SiC particle size of 100 µm produced lower friction value of 0.37 and wear rate of 2.3 x 10-4 mm3/Nm compared to 3.2 x 10-4 mm3/Nm for 20 µm particle size. The improvement of wear properties is correlated well with the increased hardness value of TIG melted hard surface layer AISI Duplex-2205 steel